Challenge and collusion: health professionals and immigration detention in Australia - Briskman, Linda; Zion, D.; Loff, B. (Routledge, 2010)
This article describes the impact of immigration detention on the health of asylum seekers. Drawing on specific examples, it explores the roles of professional staff working within the detention system and/or challenging the practices as advocates. Using oral testimony from a citizen-initiated campaign, The People's Inquiry into Detention, we interrogate the harmful experiences of force-feeding, deportation practices and the incarceration of children, including the role of the health professionals who sometimes betrayed their duty of care. Discussed are the paradoxes of dual loyalty and professional ethics.